The Influence of GrabFood on Micro Culinary Business Income Through - Ardli, Arsalan Wilyan; Bakhri, Syaeful; Layaman, Layaman (Baca Dulu Publisher, 2025)
This study aims to analyze the effect of GrabFood service usage on the income of culinary micro businesses in Cirebon City, with store ratings as an intervening variable. The method used is quantitative with a survey approach. Data collection was carried out by distributing questionnaires to 91 culinary micro business actors who use GrabFood. Data analysis was carried out using path analysis. The results showed that GrabFood usage has a positive and significant effect on store ratings, as well as business revenue. Store ratings were also shown to have a significant effect on business revenue, and partially mediate the relationship between GrabFood usage and micro business revenue. These findings indicate that optimizing services and utilizing digital platforms can improve the reputation and income of culinary micro businesses.